Material point method for large-deformation modeling of coseismic landslide and liquefaction-induced dam failure. Issue 150 (November 2021) - Feng, Kewei; Wang, Gang; Huang, Duruo; Jin, Feng
Abstract: In this study, Material Point Method (MPM) is improved to simulate coseismic slope stability and liquefaction-induced embankment failure under earthquake loading. First, by using elastic or elastoplastic models, topographic amplification and different slope failure modes are analyzed considering the effects of slope geometry, soil properties and excitation frequencies etc. The MPM model is then applied to predict a cascading slope failure process, including triggering, shear band formation, runoff and final deposition. Finally, a fully nonlinear bounding surface soil model is implemented in the two-phase soil-water coupled MPM framework to investigate the liquefaction mechanism and associated dam failure using two case histories. The numerical results are generally comparable with the post-failure profiles obtained from field investigation, which highlight the advantage of MPM in handling liquefaction-induced large deformation. The MPM shows great promise to quantitatively assess risk and consequence associated with seismic slope failure and soil liquefaction, thereby, advance the performance-based engineering design and analysis. Highlights: MPM is improved to simulate coseismic slope deformation and liquefaction-induced dam failure. Numerical examples demonstrate excellent capability of material point method in handling post-failure large deformation. Material point method has great promise to quantitatively assess seismic risk for performance-based earthquake engineering.